The Effect of Fear, Anticipation, Pessimism, and Optimism on Expertise in Using MyoB Application Version 18 - Ardiansyah, Ardiansyah (LPPM Universitas Terbuka, 2024)
This research aims to determine the influence of Fear (X1), Anticipation (X2), Pessimism (X3), and Optimism (X4) on Expertise in Using the MyoB Application (Y). The data used is primary data. Data is processed using the Partial Least Square (PLS) method with the SmartPLS application. The findings from the 4 independent variables were that 2 variables had an effect and the other 2 variables had no effect. The variables that have an influence are Anticipation (X2) and Optimism (X4), while the variables Fear (X1) and Pessimism (X3) have no effect. This means the need for anticipatory efforts and building an optimistic nature in users because it has been empirically proven to improve their skills. The novelty of this research is the difference in the placement of the independent variables consisting of Fear, Anticipation, Pessimism, and Optimism as stand-alone variables in testing, rather than being merged into the computer anxiety and computer attitude variables. Implications for higher education leaders, especially at the study program level, in adopting curriculum adjustment policies to require the use of accounting software and provide the necessary facilities for students so as to contribute positively to the quality of skilled and efficient graduates. Recommendations for future research can: (a) Expand the range of respondents; (b) Extending the duration of the research; (c) Adding research variables; (d) Testing on respondents who have practitioner status.